Toxic sports: unscreened diseases are threatening wellbeing from conception to completion of neonatal screening program - Mohamed, Mossad Abdelhak Shaban; Taher, Abdelhalim Abdelbaset; Abd Hamid, Syed Abdul Khaliq Bin; Shaban, Mohamed Mossad Abdelhak (2021)
Medical Screening is a basic test, which identifies rare and severe health problems. A newborn screening program (NSP) can detect disorders before they become symptomatic. Early treatment of these endocrine disorders can prevent intellectual disability and life-threatening crises. The hearing impairment will precipitate neurodevelopmental delay, mainly language and related skills among infants. Newborn screening for hearing loss can be done as a point-of-care screening. Universal screening for hearing loss by otoacoustic emissions or automated auditory brainstem response has a high sensitivity allowing early identification and intervention to improve the neurodevelopment among infants. Critical congenital heart disease (CCHD) can result in death, organ failure, or severe disabilities. The screening via pulse oximeter, perfusion index and echocardiography, prevent delayed diagnosis of CCHD. Developmental hip dislocation is screened clinically by Ortolani and Barlow's manoeuvres that have been the standard for detecting hip instability in newborns. Recently, ultrasound imaging of the hip in infants less than five months suggested as a possible extra tool for screening. Early screening of treatable and detectable diseases through newborn screening programs allows for timely intervention hence optimise outcomes. Keywords: Neonatal screening, Inborn error of metabolism, hearing screening, cardiac screening, Developmental Hip Dislocation screening.